Análisis del cumplimiento del modelo de gestión y la propuesta del plan de desarrollo y ordenamiento territorial del Gobierno Autónomo Descentralizado Municipal de Chone período 2014-2019 - Montesdeoca Cajape, Norma Dayana (2020)
The main objective of this investigation was to analyze the Compliance of the Management Model and the Proposal of the Development and Territorial Planning Plan of the Municipal Decentralized Autonomous Government of Chone, period 2014 to 2019, in order to verify if all the goals were concluded in that management, so it was essential to use techniques such as the interview, which was addressed to the current Mayor of Chone canton and thus obtain relevant data and information regarding its planning and the way in which it is used, as well as measures were taken to mitigate all existing shortcomings, stressing that a comparison was also made between the old and the current management in relation to PDyOT. With the use of the survey, it was possible to know what is the citizens opinion, regarding their proposed goals, in addition, all the plans, programs and projects were studied, from which it was possible to identify that this management did not comply with of the established goal, implying that its main problem itself is not so much the budget, but rather the way in which it is carried out. The PDyOT is directed so that the municipality of Chone has better control of its territories, helping to achieve the desired levels in terms of efficiency and assigned capital and at the same time to have better optimization of resources obtained, taking steps to meet the needs and requirements that are presented to newspapers in Chone canton.